De Novo Design of A Membrane‐Anchored Probe for Multidimensional Quantification of Endocytic Dynamics. Issue 8 (27th January 2022) - Qiu, Kangqiang; Seino, Ryo; Han, Guanqun; Ishiyama, Munetaka; Ueno, Yuichiro; Tian, Zhiqi; Sun, Yujie; Diao, Jiajie
Abstract: As a process of cellular uptake, endocytosis, with gradient acidity in different endocytic vesicles, is vital for the homeostasis of intracellular nutrients and other functions. To study the dynamics of endocytic pathway, a membrane‐anchored pH probe, ECGreen, is synthesized to visualize endocytic vesicles under structured illumination microscopy (SIM), a super‐resolution technology. Being sensitive to acidity with increasing fluorescence at low pH, ECGreen can differentiate early and late endosomes as well as endolysosomes. Meanwhile, membrane anchoring not only improves the durability of ECGreen, but also provides an excellent anti‐photobleaching property for long‐time imaging with SIM. Moreover, by taking these advantages of ECGreen, a multidimensional analysis model containing spatial, temporal, and pH information is successfully developed for elucidating the dynamics of endocytic vesicles and their interactions with mitochondria during autophagy, and reveals a fast conversion of endosomes near the plasma membrane. Abstract : A membrane‐anchored pH probe, with excellent durability and photostability in living cells, is developed to study the endocytic dynamics and its interaction with other organelles under nanoscopic visualization.